Tanggung Jawab Bagi Perusahaan Penyedia Jasa Pekerja Sehubungan Dengan Pelanggaran Hukum Oleh Pekerja Outsourcing di Tempat Kerja - Adfari, Tsabita Rahmah; Camilla, Garneta Rizka; Putri, Cinta Aisyah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The current outsourcing practice often receives criticism because it is considered to be detrimental to workers. The work relationships that occur are usually temporary contracts (PKWT), with lower wages, minimal social security, lack of job security, and no guarantee of career development. Therefore, it is not surprising that outsourcing practices are considered to make workers miserable and worsen industrial relations. This condition is difficult to avoid because the main motive for outsourcing is to reduce production costs. The purpose of this research is to determine who is responsible if there is a violation of the law by Outsourced Workers in the workplace and what form of responsibility is taken by the company providing Outsourced Worker services. This research uses two approaches, namely a statutory approach and a conceptual approach. Outsourcing which involves the deployment of labor and decision-making power to third parties is regulated in the Employment Law and Job Creation Law so as to ensure clarity in the operation of outsourcing services, namely in Article 66 of the Job Creation Law and PP No. 35 of 2021 regulates the responsibilities of service provider companies and service users towards outsourcing workers. Companies offering outsourced worker services must be responsible for ensuring protection, resolving disputes, and providing compensation if legal violations occur in the workplace.